An investigation into the stylistic devices commonly used in “nhat ky dang thuy tram” and their english translational equivalents in “last night, i dreamed of peace” (the diary of dang thuy tram) - Hà,Thị Hạnh (2014)
This thesis focuses on the finding of stylistic features of some commonly used stylistic devices namely simile, metaphor, rhetorical questions, repetition and personification in the Diary of Dang Thuy Tram in Vietnamese and English version, the similarities and differences between them, and the frequency of occurrences of some common used stylistic devices. The data of the study are totally collected from “Nhat Ky Dang Thuy Tram” and its English version in “Last Night I Dreamed of Peace” (The Diary of Dang Thuy Tram). It is described and contrastively analyzed on stylistic aspects under qualitative and quantitative approaches to reveal more precise points on stylistic devices. Hopefully the study is useful to those who want to know more about the Vietnamese history because the diary of Dang Thuy Tram is not only a diary but also a glorious page in history of the nation. It helps us learn more about the Vietnamese in the anti – American resistance war and respect the peaceful life that we achieved by blood and tears of millions of Vietnamese.